The civil war of 1841 and the Acha tragedy - Queseda, Ernesto (Universidad Nacional de Córdoba, 1916)
In the first part of this monograph -which I have tried to focus exclusively on Acha's actions in the civil war of 1841- I have had to draw a historical page of our annals, documenting it extensively. Now, in this second part, I must observe a different procedure, since I wish to impartially expose the antecedents of the historical lawsuit regarding the execution of the former, showing how the opinion has faced the point relative to the responsibility of who ordered such execution: for it I will try to document this exposition reproducing extensively what in this respect has come to my knowledge, as much in the elements of judgment that run printed in newspapers, magazines, pamphlets or books, as in the letters or unpublished papers that it has been possible to me to compile. In this way the scholar will be able, in the presence of all the evidence of this historical process, to draw the conclusions that are logically imposed on him and to pass the final sentence: it is time for the controversy to end and for the truth of what happened to remain firm forever.